Answer:
No solution
Step-by-step explanation:
3x + 6y =36
-3x - 6y =0
------------------add
0 ≠ 36
No solution
A. Multiplication is the ONLY function that reverses what division did. If you did 56/-14 = n, then n x -14 should equal 56.
15 - 1 = x thats the answer to the problem thats how you can have the answer
The converse would be If x² = 100 then x = -10
So essentially if the conditional statement is p → q then the converse is q → p (In essence, the converse of a conditional statement is formed by interchanging the hypothesis and the conclusion.)
-4x + 8y = 2
-4x + 4x + 8y = 2 + 4x
8y = 4x + 2
8 8
y = ¹/₂x + ¹/₄